Plasma modification of vertically aligned carbon nanotubes: Superhydrophobic surfaces with ultra-low reflectance. (February 2018) - Yung, Christopher S.; Tomlin, Nathan A.; Heuerman, Karl; Keller, Mark W.; White, Malcolm G.; Stephens, Michelle; Lehman, John H.
Abstract: Vertically aligned carbon nanotubes (VACNTs) are excellent broadband (UV–VIS–IR) absorbers of light that can be made even darker with plasma treatments. Modification of VACNTs using O2 and/or CF4 plasmas is shown to have a significant impact on the reflectance and water repellency. Unfortunately, while O2 plasma treatment reduces the reflectance of VACNTs by changing the top surface morphology, it also makes the VACNTs superhydrophilic. Using an additional CF4 plasma treatment, we show that low reflectance and superhydrophobic surfaces are possible — qualities that are desirable when utilizing VACNTs as black body absorbers in cryogenic environments due to the potential for adsorbed water or ice. Using scanning electron microscopy we show that both plasma treatments can change the surface morphology of the VACNTs similarly, which is associated with a corresponding measured reduction in spectral reflectance. Raman spectroscopy of as-grown and plasma treated samples suggest that plasma treatment is introducing defects and functionalizing the nanotube walls and thereby affecting the water repellency. O2 plasma treated VACNTs have a directional-hemispherical reflectance ( d / h ) at normal incidence ( d = 0°) of 94 ± 4 ppm (with a coverage factor of k = 2) at 660 nm and are superhydrophilic. O2 and CF4 plasma treated VACNTs have a 0°/ h reflectance of 163 ± 7 ppm ( k = 2) at 660 nm and are superhydrophobic with a contact angle of 159°. Graphical abstract: Image 1